LANDAS-BANGUN TEOLOGIS DEMOKRASI PERSPEKTIF AL-JABIRI - Muwaffiqillah, Moch. (SAMAWAT: Journal Of Hadith and Qur'anic Studies, 2022)
The struggle between Islam and democracy is a struggle between a religious institution and the state system. Islam was born in a world reality that does not have a stable power such as the state. According to al-Jabiri, political problems in Islam only started when there was a meeting between the Ansar and the Muhajirin at Saqifah Bani Saidah, after the Prophet's death, to determine the caliph. This paper will examine the theological foundations of democracy from the perspective of Muhammad 'Abid al-Jabiri, a Moroccan Islamic thinker who in his early writings elaborated on Arabic Reason (al-'Aql al-'Araby) which has attracted much attention from Muslims for his skill in explaining formation (takwin) and structure (bunyah). In contrast to Arab reasoning which is more concerned with epistemological frameworks, the conception of democracy that al-Jabiri elaborates on is also interesting because even though he accepts democracy, it does not necessarily comply with the conditions of democracy that usually develop in the West.